Lipopolysaccharide pretreatment increases the sensitivity of the TRPV1 channel and promotes an anti-inflammatory phenotype of capsaicin-activated macrophages - Vašek, Daniel; Fikarová, Natálie; Marková, Vendula Nagy; Honc, Ondřej; Pacáková, Lenka; Porubská, Bianka; Somova, Veronika; Novotný, Jiří; Melkes, Barbora; Krulová, Magdaléna (Journal of inflammation, 2024)
BACKGROUND: The transient receptor potential vanilloid 1 (TRPV1) is well-established in neuronal function, yet its role in immune reactions remains enigmatic. The conflicting data on its inflammatory role, suggesting both pro-inflammatory and anti-inflammatory effects upon TRPV1 stimulation in immune cells, adds complexity. To unravel TRPV1 immunomodulatory mechanisms, we investigated how the TRPV1 agonist capsaicin influences lipopolysaccharide (LPS)-induced pro-inflammatory macrophage phenotypes. RESULTS: Changes in the surface molecules, cytokine production, and signaling cascades linked to the phenotype of M1 or M2 macrophages of the J774 macrophage cell line and bone marrow-derived macrophages, treated with capsaicin before or after the LPS-induced inflammatory reaction were determined. The functional capacity of macrophages was also assessed by infecting the stimulated macrophages with the intracellular parasite Leishmania mexicana. CONCLUSION: Our findings reveal that TRPV1 activation yields distinct macrophage responses influenced by the inflammatory context. LPS pre-treatment followed by capsaicin activation prompted increased calcium influx, accompanied by a shift toward an anti-inflammatory M2b-like polarization state.